Entre vanguarda e a participação: a democracia no programa político da esquerda brasileira (1930-1935) - Cintra, Wendel Antunes [UNESP] (My University, 2014)
This paper examines the conceptions of democracy in the Brazilian left among 1930-1935, in particular those expressed in the manifestos of the National Liberative Alliance (ANL) and the texts written by Luis Carlos Prestes, Virgínio Santa Rosa and Caio Prado Jr. I argue that the Brazilian left started from a common troubled field, according to which land concentration represented the biggest obstacle to genuine political expression of the Brazilian people. Despite the convergence towards land reform, designed as a sine qua non condition to democracy in Brazil, the left has developed two different answers to the practical implementation of the principle of the people's government: the first, which I call altruist vanguard, which is more emphasized on texts of Virgínio Santa Rosa and Luís Carlos Prestes, and the second, the Republican participacionismo, which is explored on the writings of Caio Prado Jr. and ambiguously in the manifests of the National Liberative Alliance.

El artículo examina las concepciones de la democracia en la izquierda brasileña entre 1930-1935, en particular, los que se expresan en los manifiestos de la Alianza para la Liberación Nacional (ANL) y los textos escritos por Luís Carlos Prestes, Virgínio Santa Rosa y Caio Prado Jr. Yo sostengo que la izquierda brasileña venía de un área problemática común, según la cual la concentración de la tierra representaba el mayor obstáculo para la verdadera expresión política del pueblo brasileño. A pesar de la convergencia hacia la reforma agraria, diseñado como una condición sine qua non para la democracia en Brasil, la izquierda ha desarrollado dos respuestas diferentes a la aplicación práctica del principio de gobierno popular: la primera, que yo llamo vanguardia abnegada, que está más presente en los textos de Virgínio Santa Rosa y Luís Carlos Prestes, y el segundo, el participacionismo republicano, presente en los escritos de Caio Prado Jr. y ambiguamente presente en los manifiestos de la Alianza para la Liberación Nacional.

O artigo examina as concepções de democracia na esquerda brasileira entre 1930-1935, em particular aquelas expressas nos manifestos da Aliança Nacional Libertadora (ANL) e nos textos escritos por Luís Carlos Prestes, Virgínio Santa Rosa e Caio Prado Jr. Argumento que a esquerda brasileira partia de um campo problemático comum, segundo o qual a concentração fundiária representava o maior obstáculo para a autêntica expressão política do povo brasileiro. A despeito da convergência em torno da reforma agrária, pensada como condição sine qua non para a democracia no Brasil, a esquerda desenvolveu duas respostas distintas para a realização prática do princípio do governo do povo: a primeira, que denomino vanguarda altruísta, presente com maior ênfase nos textos de Virgínio Santa Rosa e Luís Carlos Prestes, e a segunda, o participacionismo republicano, explorada nos escritos de Caio Prado Jr. e, de modo mais ambíguo, nos manifestos da Aliança Nacional Libertadora.
Between vanguard and participation: democracy in the political program of the Brazilian left (1930-1935)
Entre vanguardia y participación: la democracia en programa politico de la izquierda brasileña (1930-1935)
Keywords: Democracy; Land Reform; Tenentismo; National Liberative Alliance (ANL); Democracia; Reforma Agraria; Tenentismo; Alianza para la Liberación Nacional (ANL); Democracia; Reforma Agrária; Tenentismo; Aliança N